Perancangan Sistem Kontrol Kelistrikan Otomatis Kompor Listrik Halogen Berbasis Mikrokontroler - Juliem Zulfadli; Habibullah Habibullah (Jurnal Teknik Elektro Indonesia, 2021)
Abstract- The stove is one of the main tools used in households. Used to heat an object in the form of food. In its development, the stove used for cooking has experienced many advances, one of which is an electric stove. Currently electric stoves on the market, especially the electric stove, halogen heater, single ceramic stove, are available in the form of a rotary switch on / off. The purpose of writing this scientific research is to design an automatic control system on this single ceramic stove type halogen electric stove. Where previously stove control using only a rotary switch was changed to automatic control via a keypad in the form of a timer and temperature input with a digital display via LCD. The electrical components used are the Arduino Mega 2560 microcontroller as the control center, MAX6675 as a temperature sensor, ACS712 sensor to read current values, ZMPT101B sensor to read voltage values, relay as electric switch, buzzer as alarm, keypad as input and LCD as display output on electric stove. The results of this design were obtained in accordance with what was the goal of this scientific research where previously the electric stove was manually controlled to be converted into automatic control by inputting the required temperature value and working based on the temperature setpoint input and displaying the amount of energy released on the electric stove. Keywords— Arduino Mega 2560 Microcontroller, MAX6675, LCD, Keypad, Halogen Electric Stove.